2001
DOI: 10.1159/000050015
|View full text |Cite
|
Sign up to set email alerts
|

Antipituitary Antibodies in Patients with Lymphocytic Hypophysitis

Abstract: Background: Lymphocytic hypophysitis is one of the causes of hypopituitarism, which is considered an autoimmune reaction in the anterior pituitary. Method: We examined antipituitary antibodies in patients with lymphocytic hypophysitis and related diseases by immunoblotting method. Results: Autoantibodies to a 22-kDa human pituitary cytosolic protein were identified in significantly higher frequencies in sera from patients with lymphocytic hypophysitis (11 of 15, 73.3%) and isolated ACTH deficiency (7 of 9, 77.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
51
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 10 publications
2
51
0
1
Order By: Relevance
“…APAs are often detected in several pituitary diseases [1][2][3]. However, it is unclear whether the detected APAs are related to the etiology or are consequences of the disease.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…APAs are often detected in several pituitary diseases [1][2][3]. However, it is unclear whether the detected APAs are related to the etiology or are consequences of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous report [1], APA, the antibody to the human pituitary cytosol was detected in five of six patients with isolated TSH deficiency. APAs were detected also in patients with isolated ACTH deficiency [2,4,34,35] and empty sella [34,35]. It is suggested that LAH as an autoimmune disease contributed to the etiology of isolated TSH deficiency in some of the patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations